ANALISIS SOSIO YURIDIS PEMBINAAN DI LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS IIA SUNGGUMINASA GOWA: JURIDICAL SOCIO ANALYSIS OF DEVELOPMENT IN CLASS IIA WOMEN'S CORRECTION INSTITUTION SUNGGUMINASA GOWA - Masykur, Fadhilah Azhilah; Madiong, Baso; Kamsilaniah (Clavia, 2020)
This research aims to know more about how the implementation of the construction in the LPP class IIA is a part of the Gowa and to know the obstacles that become the obstacle of coaching that is done by LPP class IIA although Gowa. The method of use is the type of socio juridical. The method of socio juridical research is to use field data or commonly called empirical data. According to the scholars of the empirical research experts he thinks it is not a real legal research but rather this social research, because sixty percent of data needed is field input instead of normatife data and or the library Do normative law, but empirical research will not be able to be expressed purely overall social research, because the contents therein there are several discussions that have been contained between the facts in the community and the rules of Referu and the theory of The law that is written. As well as the kinds and info data authors use in this data namely secondary and Premier. The results of this research show that the target in LPP class II A have been optimal through the formation of pricy, among others education and teaching, sports, art activities, as well as spiritual activities and self-reliance coaching which include Skills such as manufacturing bosara, knitted, sewing, making tissue place as well as vases and as for the obstacles that become natural inhibitory in the LPP class IIA despite the lack of other facilities and infrastructures in the prison and Constraints of lack of outside construction, still requiring cooperation or MOU from outside parties to assist the construction of the target residents.